Broiler Microbiological and Histological Response to Diets Varying in Sodium and Calcium Butyrate (Texas Journal of Agriculture and Biological Sciences, 2023)
The aim of the study was to determine the effect of supplementing broiler diets with different levels of sodium and calcium butyrate on certain histological and microbial traits. This study was conducted in the poultry field of the Department of Animal Production at the College of Agricultural Engineering Sciences / University of Baghdad (Baghdad, Iraq) during November - December (2020) in a total of 308 one-day-old chicken utilized in the study, and each treatment had three replicates consisting of 10 chicks each. Duodenal villi height increased significantly (p